A review of the cleptoparasitic bee genus Triepeolus (Hymenoptera: Apidae).-Part I - Rightmyer, Molly G. (Zootaxa, 2008)
The cleptoparasitic bee genus Triepeolus is a widespread, species-rich group that has never been revised throughout its geographic range. Herein I review 103 species of Triepeolus, including all but those that belong to the newly defined Triepeolus verbesinae and Triepeolus simplex species groups (these will be the topic of a subsequent paper). I present three keys to the species, which together cover the genus throughout its range in the New World; the keys are to the females of North and Central America, the males and females from Eastern North America, and the males and females from South America and the Caribbean. I propose the following 37 new species: Triepeolus antiochensis, T. argentimus, T. argus, T. bimorulus, T. charlesi, T. circumculus, T. claytoni, T. cruciformis, T. diffusus, T. dilutus, T. edwardi, T. engeli, T. exilicurvus, T. flavigradus, T. fulgidus, T. griswoldi, T. interruptus, T. isohedrus, T. jennieae, T. joliae, T. lateralis, T. margaretae, T. mauropygus, T. melanarius, T. micheneri, T. nayaritensis, T. parkeri, T. partitus, T. parvidiversipes, T. parvus, T. perpictus, T. phaeopygus, T. punctoclypeus, T. quadratus, T. simulatus, T. vernus, and T. warriti, and propose the new combinations Triepeolus laticeps (Friese), Triepeolus tepanecus (Cresson) and Triepeolus zacatecus (Cresson). I newly synonymize 45 of the 169 previously proposed Triepeolus names, for a total of 51 synonymies: T. alachuensis Mitchell under T. rufithorax Graenicher; Epeolus albopictus Cockerell, E. costaricensis Friese, and E. flavocinctus Friese under T. aztecus (Cresson); T. alpestris Cockerell, T. amandus Cockerell, and T. vandykei Cockerell and Sandhouse under T. paenepectoralis Viereck; E. bardus Cresson, T. mesillae Cockerell, and T. pimarum Cockerell under T. distinctus (Cresson); T. brunneus Cockerell under T. balteatus Cockerell; T. charlottensis Mitchell under T. brittaini Cockerell; T. cirsianus Mitchell under T. donatus (Smith); T. concinnus Cockerell under T. townsendi Cockerell; T. coquilletti Cockerell, T. helianthi arizonensis Cockerell, T. helianthi pacificus Cockerell, T. lineatulus Cockerell and Sandhouse, and T. maculiventris Cockerell under T. helianthi (Robertson); T. dichropus Cockerell, T. eldredi Cockerell, T. helianthi grandior Cockerell, T. pallidiventris Cockerell and Sandhouse, T. rectangularis Cockerell, and T. wyomingensis Cockerell under T. texanus (Cresson); T. digueti Cockerell and E. nobilis Friese under T. intrepidus (Smith); T. floridanus Mitchellunder T. georgicus Mitchell; T. fortis Cockerell, T. insolitus Cockerell, and T. trilobatus Cockerell under T. martini (Cockerell); T. foxii Cockerell under T. rufoclypeus (Fox); T. lestes Cockerell under T. subalpinus Cockerell; T. loganensis Cockerell and T. sandhousae Cockerell under T. fraserae Cockerell; T. nautlanus Cockerell under T. lunatus (Say); E. nigriceps Smith under T. robustus (Cresson); E. oswegoensis Mitchell under T. pectoralis (Robertson); T. perelegans Cockerell and T. trichopygus Cockerell and Timberlake under T. penicilliferus (Brues); T. signatus Hedicke under T. ventralis (Meade-Waldo); T. stricklandi Cockerell under T. subalpinus Cockerell; E. superbus Provancher and E. texanus nigripes Cockerell under T. remigatus (Fabricius); and E. utahensis Cockerell under T. heterurus (Cockerell and Sandhouse).